1977
DOI: 10.1002/jso.2930090605
|View full text |Cite
|
Sign up to set email alerts
|

Serum polyamine alterations in surgical patients with colorectal carcinoma

Abstract: Polyamines, by virture of their regulatory role in the cellular synthesis of DNA, RNA, and protein, are potential indicators of malignant growth. In view of this, serum polyamine levels of patients with colorectal carcinoma or benign bowel disease were examined. Of 53 patients with colorectal carcinoma, 35 (66%) showed elevations of 1 or more polyamines. Nine patients with benign bowel disease (villous adenoma, Gardner's syndrome, familial polyposis, and diverticulitis) showed normal serum polyamine levels exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 6 publications
1
6
1
Order By: Relevance
“…Our observations are in good agreement with those obtained by others [15][16][17] in respect to PUT and SPD. SPM, however, was found to be significantly elevated in the patients of Nishioka et al [15], in con trast to our findings.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our observations are in good agreement with those obtained by others [15][16][17] in respect to PUT and SPD. SPM, however, was found to be significantly elevated in the patients of Nishioka et al [15], in con trast to our findings.…”
Section: Discussionsupporting
confidence: 83%
“…SPM, however, was found to be significantly elevated in the patients of Nishioka et al [15], in con trast to our findings. The reason for the difference be tween the values in the literature and ours for SPM should be considered with regard to the different meth ods of sample preparation, i.e., in the extraction of total and free polyamines.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…These findings suggest the possibility that common factor(s), not specifically produced in cancer patients, can induce immunosuppressive conditions. Polyamines are one such factor, because blood polyamine levels, namely levels in blood cells including immune cells, are often increased in patients with various diseases [36,95-97]. …”
Section: Mechanism Of Metastasis and Involvement Of Polyamines (Fimentioning
confidence: 99%
“…Numerous studies have been published evaluating the clinical usefulness of these two polyamines in the diagnosis and treatment of many types of malignant disease (3)(4)(5)(6)(7)(8)(9)(10). One study reported putrescine levels to be a reliable biochemical marker of brain tumors (11).…”
Section: Introductionmentioning
confidence: 99%